Automation Processes for Enterprise Architecture Management - Farwick, M.; Agreiter, B.; Breu, R.; Ryll, S.; Voges, K.; Hanschke, I. (2011 IEEE 15th International Enterprise Distributed Object Computing Conference Workshops, 2011)
Creating and maintaining an enterprise architecture model that is both up-to-date and accurate is a difficult task due to the size and complexity of the models and the dispersed nature of EA information in organizations. In current EA maintenance processes, the models are maintained manually with only little automation, which is a time consuming task. Literature from research and practice has identified this challenge, but only few scientific publications actually address the issue of EA model maintenance and its automation. In our research effort on Living Models, we are working towards solutions for a closer connection between EA models and what they represent in the real world. In this article we present (semi-)automated processes for maintaining enterprise architecture models by gathering information from both human input and technical interfaces and discuss implementation issues for realizing the processes in practice. This work is one of the first steps in the direction of minimizing manual work for EAM by automation and increasing EA data quality attributes such as consistency and actuality.